ISLAM, HAM, DAN KEBEBASAN INFORMASI (Telaah Kritis UU No. 39Tahun 1999) - A. Rajamuddin (Program Studi Ilmu Agama Islam Program Magister, Universitas Islam Indonesia, 2012)
This paper discusses the freedom of obtaining information in Islam in the human rights perspective by examining critically act of number 39 of 1999. The law explains that in the dynamic growth of democracy country, freedom of getting information is a main thing. Therefore, involvement of the people to take part requires the presence of rules that creates an open environment system in order that what is to be every citizen's right is met. Law of number 39 of 1999 regulates in detail about freedom of information. The results of the analysis confirmed that implementation of law of number 39 of 1999 has not got optimal because itis not supported by humanist country climate.